2021
DOI: 10.1532/hsf.3777
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery–Left Ventricular Fistula with Giant Right Coronary Aneurysm: A Case Report and Literature Review

Abstract: Right coronary artery–left ventricular (RCA–LV) fistula with associated giant right coronary artery aneurysm (CAA) is an extremely rare cardiac condition. This case study presents a patient with a large left ventricle (LV) and a giant right CAA with a maximal inner diameter of approximately 56.6 mm and an inner diameter of approximately 22 mm at its communication with the left ventricle. The patient underwent surgical management, involving suturing of the proximal end of the CAA and coronary artery bypass graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In this case, coronary CTA efficiently delineated the origin, fistulous tracts, and drainage site of coronary artery fistula and comprehensive details of coronary aneurysm, increasingly recognised as the imaging method of choice for coronary artery diseases. 6 Coronary angiography contributed further details. Notably, in this case, coronary angiography revealed that the left anterior descending coronary artery received retrograde supply from the right coronary artery, suggesting the aneurysm involved the left main coronary artery and the left circumflex coronary artery, with the proximal segment of the left anterior descending coronary artery occluded.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, coronary CTA efficiently delineated the origin, fistulous tracts, and drainage site of coronary artery fistula and comprehensive details of coronary aneurysm, increasingly recognised as the imaging method of choice for coronary artery diseases. 6 Coronary angiography contributed further details. Notably, in this case, coronary angiography revealed that the left anterior descending coronary artery received retrograde supply from the right coronary artery, suggesting the aneurysm involved the left main coronary artery and the left circumflex coronary artery, with the proximal segment of the left anterior descending coronary artery occluded.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery atherosclerosis, Kawasaki disease, coronary artery dysplasia and trauma can lead to coronary artery aneurysm ( 9 ). However, the above reasons cannot explain the coronary artery dilation and CAA formation in this CAF patient.…”
Section: Discussionmentioning
confidence: 99%
“…A CCF that drains to the left ventricle (LV) produces hemodynamic changes similar to those of aortic regurgitation, and a CCF that drains to the left atrium (LA) results in volume overload similar to that of mitral regurgitation [6]. If left untreated, CCFs may result in clinical complications, such as myocardial ischemia [7], ventricular dysfunction [8], aneurysmal formation [9], and infective endocarditis [10].…”
Section: Introductionmentioning
confidence: 99%